2013
DOI: 10.1063/1.4795326
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pressure on the phase stability of nanocomposite Fe89Zr7B4 during heating from energy dispersive x-ray diffraction

Abstract: Nanocomposite materials consisting of small crystalline grains embedded within an amorphous matrix show promise for many soft magnetic applications. The influence of pressure is investigated by in situ diffraction of hammer milled Fe89Zr7B4 during heating through the α → γ Fe transition at 0.5, 2.2, and 4.9 GPa. The changes in primary and secondary crystallization onset are described by diffusion and the energy to form a critical nucleus within the framework of classical nucleation theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ingots were melt-spun to quench the alloys and retain a single, disordered FCC phase. Energy dispersive x-ray diffraction measurements were taken in a Paris-Edinburgh cell [33]- [35] at the HPCAT 16-BM-B high pressure station at Argonne National Lab's Advanced Photon Source. They were converted to conventional angle-dispersive spectra using Bragg's law.…”
Section: Experimental Procedurementioning
confidence: 99%
“…Ingots were melt-spun to quench the alloys and retain a single, disordered FCC phase. Energy dispersive x-ray diffraction measurements were taken in a Paris-Edinburgh cell [33]- [35] at the HPCAT 16-BM-B high pressure station at Argonne National Lab's Advanced Photon Source. They were converted to conventional angle-dispersive spectra using Bragg's law.…”
Section: Experimental Procedurementioning
confidence: 99%
“…Ohodnicki et al 29 detailed crystallization in Co-rich (Co, Fe)-based amorphous alloys. Leary et al 30 reported pressure effects in NANOPERM Fe-based MANCs.…”
Section: Manc Synthesis Chemistry and Property Developmentmentioning
confidence: 99%